1976
DOI: 10.1007/bf00385428
|View full text |Cite
|
Sign up to set email alerts
|

Auxin in scapes, flower buds, flowers, and fruits of daffodil (Narcissus pseudonarcissus L.)

Abstract: Diffusates from flower buds, flower fruits, and scape segments, and extracts of flower stalks of Narcissus pseudonarcissus contain an auxin active in the Avena geo-curvature test. The auxin behaved like indole-3-acetic acid (IAA) in thin-layer chromatography (TLC) with neutral and basic solvents on different adsorbents. After TLC, the auxin of the extracts showed chromogenic reactions identical with those of IAA; in gas-liquid chromatography on two different columns, the purified substance, after methylation, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

1977
1977
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 9 publications
1
9
0
Order By: Relevance
“…5). A similar effect of flower stalk growth inhibition upon bud decapitation or emasculation was observed in the miniature Cymbidium orchid (Ohno and Kako 1991), the tulip (Hanks and Rees 1977;Saniewski and De Munk 1981), and the daffodil (Edelbluth and Kaldewey 1976;Hanks and Rees 1977).…”
Section: Impact On Peduncle Elongation and Vascular Anatomysupporting
confidence: 64%
See 1 more Smart Citation
“…5). A similar effect of flower stalk growth inhibition upon bud decapitation or emasculation was observed in the miniature Cymbidium orchid (Ohno and Kako 1991), the tulip (Hanks and Rees 1977;Saniewski and De Munk 1981), and the daffodil (Edelbluth and Kaldewey 1976;Hanks and Rees 1977).…”
Section: Impact On Peduncle Elongation and Vascular Anatomysupporting
confidence: 64%
“…It was observed that removal of the flower or floral organs inhibits the elongation of the floral stalk or peduncle (Op den Kelder and others 1971;Hanks and Rees 1977). Treatment of emasculated or decapitated flowers with auxins (Edelbluth and Kaldewey 1976;Hanks and Rees 1977;De Munk 1979;Kohji and others 1979;Saniewski and De Munk 1981;Ohno and Kako 1991), as well as treatments of isolated stalk explants (Gabryszewska and Saniewski 1983), led to the conclusion that these plant hormones originating in anthers, gynoecium, or developing fruit are largely responsible for peduncle elongation. Identification of endogenous hormones during flowering in the tulip (Okubo and Uemoto 1985;Xu and others 2008) and barley (Wolbang and others 2004) confirm that diffusible auxins from floral organs, in the first place, and in coordination with gibberellins are responsible for stalk elongation.…”
Section: Introductionmentioning
confidence: 99%
“…This phytohormone is supplied from flower buds whose development is stimulated by GA3, or by low temperature. The supply of auxin by the developing flower buds was also noted in other plants (3,7,13). The effectiveness of GA on flower stalk elongation is different among plant species.…”
Section: Discussionmentioning
confidence: 78%
“…This ester is readily detected in the GC-column effluent by a flame ionization detector (FID), which is the most widely used detector system because it has sensitivity limits approaching 1 ng for almost all organic compounds. This ester was used in the identification of IAA in maize seeds (Powell, 1964), in tobacco shoots (Bayer, 1969), and in flower buds, flowers, and fruits of daffodil (Edelbluth and Kaldewey, 1976), where identification was based on co-chromatography with authentic Me-IAA and spectrophotofluorimetry. Me-IAA was also employed for identifying IAA in maize roots (Elliott and Greenwood, 1974) and in shoots of Douglass fir (DeYoe and Zaerr, 1976) using GC-l1S procedures.…”
Section: Gas-liquid Chromatography Of the Growth Regulator In Plant Ementioning
confidence: 99%